Acute and late coronary outcomes in 1073 patients with Kawasaki disease with and without intravenous γ-immunoglobulin therapy. Issue 6 (6th January 2015) - Lin, Ming-Tai; Sun, Li-Chuan; Wu, En-Ting; Wang, Jou-Kou; Lue, Hung-Chi; Wu, Mei-Hwan
Abstract : Objective: To explore acute and late coronary outcomes and their risk/modifiers in patients with Kawasaki disease (KD). Design: Retrospective study. Setting and patients: 1073 patients with KD identified from a tertiary care medical centre (1980–2012; 8677 patient-years). Main outcome measures: The acute coronary severities and late outcomes (survival free of coronary aneurysm persistence and ischaemia) were assessed. Results: Coronary arterial lesions occurred in 40.6% of cases at their acute febrile stages, and persisted beyond 1 month in 196 (18.3%, M/F=138/58) patients: 125 (11.6%) had small aneurysms, 44 (4.1%) had medium aneurysms, and 27 (2.5%) had giant aneurysms. At follow-up (1–46 years), coronary aneurysms persisted in all with giant aneurysms, in 55% of those with medium aneurysms (18% with stenosis), and in 9% of those with small aneurysms. Ischaemia events occurred in 14 patients (M/F=13/1) and caused four deaths. Among the patients with KD with coronary aneurysms, 10-year ischaemia event-free and aneurysm persistence probability was 87.5% and 20.6%, respectively. The only independent risk for aneurysm persistence was the aneurysm severity 1 month after KD onset (χ 2 =80.73, p<10 −3 ). Male patients and intravenous γ-immunoglobulin (IVIG) therapy were independent risk factors of initial coronary severity but were not associated with the late coronary outcomes, even in severity stratified subgroups. Conclusions: The coronary severity 1 month after KD onset is most crucial to the late coronary outcomes. Although IVIG use improves the initial severity of coronary lesions, it does not further modify the long-term fate of coronary aneurysms.